GENES THAT WE CHANGE - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The gene already is no characterized as "closed" stationary system of keeping of the hereditary information. It is plastic material and it can respond sensitively to changes of internal and external environment of man. The food, the diet, the physical activity, the level of stress, the bad habits and the ecology influence on expression of our genes and on genom overall.